Effect of temperature on fatty acid composition and development of unfed Siberian sturgeon (A. baerii) larvae. (18th May 2018) - Vasconi, Mauro; Aidos, Lucia; Di Giancamillo, Alessia; Bellagamba, Federica; Domeneghini, Cinzia; Moretti, Vittorio M.
Abstract: The fatty acid metabolism in fish is influenced by various factors, including fish species, water temperature, water environment and diet supply. The aim of present work is to investigate the fatty acid composition of yolk‐stage Siberian sturgeon larvae reared at three different temperatures. Fertilized Siberian sturgeon eggs were transferred to the Lodi Aquaculture Research Center of the University of Milan, divided in three aquaria, each containing three incubators and incubated at 16°C. After hatching the temperature was switched to 16, 19 and 22°C. Larvae sampling was performed at the end of yolk sac reabsorption. No feed was dispensed during the trial. Eggs and larvae were weighed and fatty acid profile was determined by GC‐FID analysis after lipid extraction by chloroform/methanol mixture and fatty acid transesterification by methanolic hydrogen chloride. The fertilized eggs had a weight of 23.27 mg and a lipid content of 2.67 mg/egg. At hatching, the weight was 12.2 (0.17 SD ) mg and lipid content 1.9 (0.6 SD ) mg/larva. At the end of the trial, larvae mean weight was 33.6 (3.6 SD ), 34.7 (1.8 SD ) and 36.9 (1.1 SD ) mg, while lipid content was 2.0 (0.3 SD ), 2.1 (0.3 SD ) and 2.0 (0.2 SD ) mg for larvae reared at 16, 19 and 22°C respectively, without statistically significant difference. Larvae subjected to the highest water temperature showed a faster yolk‐sac absorption. No differences were found across temperatures regarding survival rates and regarding ontogenic development. The fatty acid composition of larvae was affected by the temperature. Larvae reared at 16°C had the lowest amount of saturated fatty acids, mainly due to a lower palmitic acid content, that was offset by a higher level of linolenic and linoleic acid, if compared with larvae reared at 19°C and 22°C. The study suggests that at a lower temperature sturgeon spare unsaturated fatty acid consuming preferably saturated fatty acids, increasing our knowledge of the fatty acid metabolism in this species.